The Phenomenon of Hydrogen Embrittlement in High-Strength Bolts - T. Dubiel; T. Balawender; M. Osetek (Archives of Metallurgy and Materials, 2023)
The hydrogen embrittlement of metals is caused by the penetration and accumulation of hydrogen atoms inside the metal. The failure of the product due to hydrogen embrittlement is delayed in time and does not occur immediately after its manufacture, but several hours, days, or even weeks later. Therefore, the chances of detecting hydrogen embrittlement when checking the quality of the finished product are very slim. The use of high-strength bolts in industry is associated with the risk of hydrogen embrittlement. This phenomenon poses a threat to the safe use of devices by limiting or completely losing the functionality of the bolt joint. Even a low influence of moisture can trigger failure mechanisms. The article proposes a method for assessing the risk of hydrogen embrittlement for high-strength bolts in class12.9. For this purpose, bolts made of material grade 32CrB4 were prepared and in a controlled manner the grain flow inconsistency was made, leading in extreme cases to the production of the forging lap. To perform the study, the device proposed by the European Assessment Document (EAD) was adapted to the testing of hydrogen embrittlement of threaded fasteners in concrete. The concrete substrate was replaced with metal spacers that were preloaded with a bolt. The use of the wedge distance under the bolt head led to the generation of two stress states – tensile and compressive, which translated into an increased risk of hydrogen embrittlement. After being tested, the bolts were visually and microscopically inspected to assess potential locations for cracks and hydrogen propagation. As a result of the conducted tests, it was found that the prepared test method allows to assess the resistance or susceptibility of the bolt to threats related to hydrogen embrittlement.